Mbesan Wedding Tradition in Banyumas, Banjarnegara, Cilacap and Purbalingga (Study of Culture and Religion) - Fransisca, Malia; Idi, Abdullah; Syawaluddin, Muhammad (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2024)
This article wants to reveal the phenomenon of wedding traditions that exist in the Karisedenan area of Banyumas (Banyumas, Banjarnegara, Cilacap and Purbalingga). This wedding tradition in called mbesan. In practice, this mbesan tradition before holding a wedding ceremony at the bride’s house (reception), there is an event such as praying for the bride and groom before sailing the ship of the next life. The mbesan tradition is carried out at the groom's house, but the two brides do not yet have a marriage contract. The purpose of writing this article is to inform the public that Indonesia is rich in traditions, one of which is the mbesan tradition which is the hallmark of the Banyumas area and its surroundings and the impact of this mbesan tradition. The method used in this research is qualitative with phenomenological, sociological and cultural approaches. The results of this study found that in the mbesan tradition which has become the customs of the people of Banyumas, Cilacap, Purbalingga and Banjarnegara there are sides that are not in accordance with Islamic teachings because in practice the bridegroom and bride carry out the event at the groom but both have not yet carried out the marriage contract.